2021
DOI: 10.1108/jrit-01-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Students' perceived benefits, adoption intention and satisfaction to technology-enhanced learning: examining the relationships

Abstract: PurposeProviding quality education with the help of technologies in order to create global competitiveness among the students is the current trend in the education field. This research attempts to investigate following objectives: (1) the effect of students' perceived benefits and adoption intention of technology-enhanced learning (TEL) on their satisfaction; (2) the effect of students' perceived benefits of TEL on their adoption intention of TEL; (3) the mediating and moderating effect of students' perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 71 publications
(72 reference statements)
4
39
0
Order By: Relevance
“…The effect of e-learning on learner satisfaction has been widely researched. This finding is consistent with findings from previous research (Tarhini et al, 2017;Kurucay and Inan, 2017;Dubey and Sahu, 2021;Quadir et al, 2022). It can be concluded that the adoption of e-learning systems in developing economies will result in improved Learner satisfaction in higher education learner satisfaction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of e-learning on learner satisfaction has been widely researched. This finding is consistent with findings from previous research (Tarhini et al, 2017;Kurucay and Inan, 2017;Dubey and Sahu, 2021;Quadir et al, 2022). It can be concluded that the adoption of e-learning systems in developing economies will result in improved Learner satisfaction in higher education learner satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…The concept of e-learning has been adopted world-over, as a revolution in the educational field, to better the traditional modes of learning and build capacity in education and training (Alfraih and Alanezi, 2016;Tarhini et al, 2017). The phenomenon has been implemented either haphazardly or in a calculated move, in order to enhance the knowledge and skills of students as demanded in the 21st century (Dubey and Sahu, 2021). A smooth e-learning environment is a prerequisite to effective learning and learner satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Herzberg (1959) hygiene-motivation theory which asserts that the hygiene factors are taken for granted factors that does not really make a difference in satisfaction, the research finding indicated that students value the interactional/process more than the core/hygiene aspect. On the other hand, this finding also coincides with the findings that the perceived usefulness is the strongest predictors of satisfaction (Dubey & Sahu, 2021;Liaw & Huang, 2013). All of these findings suggest that the higher education institutions should focus more on the interactional/process and utility/benefit aspects of the quality to achieve high student satisfaction with the lowest possible cost.…”
Section: Strategic Management Map (Smm)supporting
confidence: 85%
“…Task and technological characteristics contribute to students' perceived usefulness of learning tools and satisfaction with them. This leads to continued intention to use them (Dubey and Sahu, 2021). The right mix of e-learning tools is required to mediate the learner's interaction with educational content to facilitate knowledge construction.…”
Section: Virtual Campuses In Developing Countriesmentioning
confidence: 99%
“…This study makes use of Queiros and de Villiers' Model (2016) of vital connections for the online learner as its conceptual framework. The framework allows for the assessment of learning to include learner input, learning environment and output (Ng, 2017;Tarhini et al, JRIT 2017; Dubey and Sahu, 2021). The framework allows for a quantitative study on the relative importance of e-learning facets (connectors) of technological self-efficacy, social presence and learning tools on e-learning satisfaction (see Figure 1).…”
Section: Conceptual Framework Of the Studymentioning
confidence: 99%